Do Firms Use Restructuring Charge Reversals to Meet Earnings Targets? - Moehrle, Stephen R. (The Accounting Review, 2002)
Many firms that take restructuring charges reverse a portion of those restructuring charge accruals in a later quarter. These reversals increase net income, often substantially. In this study, I investigate whether restructuring charge reversals are associated with incentives to meet or exceed analysts' forecasts, avoid earnings declines relative to prior-year levels, and avoid losses. I examine both the decision to record a reversal and the amount of the reversal, using a sample of 121 reversals recorded between 1990 and 1999. The results suggest that some firms record reversals to beat analysts' forecasts and to avoid reporting net losses. There is also some evidence that firms record reversals to avoid earnings declines. Overall, the results are consistent with firms using restructuring accrual reversals to manage earnings.